A new species of genus Phonarellus Gorochov, 1983 from Yunnan, China (Orthoptera: Gryllidae: Gryllinae) - Liu, Yi-Jiao; He, Zhu-Qing (Zootaxa, 2022)
Phonarellus Gorochov, 1983 is comprised of 11 extant species. We describe a new species, Phonarellus (Phonarellus) zebripes He sp. nov. from Yunnan province, China. It is different from other Phonarellus species in possessing black and white stripes on the hind femora. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).